Dual Bioelectrical Impedance Analysis Correlates Well with Computed Tomography to Estimate Visceral Fat in Grade I-II Obese Mexican Patients - Muñoz, Ernesto G. Cardona; Páez, Fernando Grover; Becerra, Carlos Gerardo Ramos; Sutto, Sylvia E. Totsuka; Sánchez, Guillermo Adrián Alanis; Corral, Jesús Ricardo García; Aguilar, Catherine A. García; Iantchoulev, Assen Ognianov; Bernal, José Rafael Villafán; Barajas, Ana Leticia Milanés (ABC Journal of Advanced Research, 2014)
Objective: To correlate visceral fat using bioelectrical impedance analysis (Dual BIA) with computed tomography (CT) in Grade I-II Obese Mexican Patients. Research Design and Methods: We recruited 30 Mexican patients from the western part of the country (15 men and 15 women, aged 50-65 years) with class I-II obesity (body mass index [BMI] 30-39.9 Kg/m2). To evaluate the IAFA by Dual BIA comparing with CT.The dual BIA instrument consists of a bioelectric impedance component that measures the physical size of the abdomen. The truncal impedance is measured by applying electrical currents between the upper and lower limb leads and reading the voltage from the electrodes around the abdominal circumference. The surface impedance is measured by applying and measuring the voltage from the abdominal circumference electrodes. We took computed tomography (CT) at the umbilical level and calculated the visceral fat area (VFA).BMI was calculated as body weight (in kilograms) divided by the squared height (in meters). Waist circumference (WC) was measured at the level of the umbilicus to the nearest 0.1 cm in the standing position at the end of expiration. Results: We observed a strong correlation between both methods used to calculate IAFA (BIA and CT; Pearson’s r2 =0.659, p < 0.001). Though both groups had significantly correlating values, the female group had a clearly stronger correlation than the male group (Pearson’s r2 = 0.667 vs. 0.501). This method exhibited a high level of reproducibility and a strong correlation with the CT results.